Photodynamic potential of curcumin and blue LED against streptococcus mutans in a planktonic culture - Paschoal, Marco Aurelio [UNESP]; Tonon, Caroline C. [UNESP]; Spolidório, Denise M.P. [UNESP]; Bagnato, Vanderley S.; Giusti, Juçaíra S.M.; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (My University, 2013)
Background: The photodynamic therapy (PDT) involves the use of light of specific wavelength to activate a nontoxic photosensitizing agent or dye in the presence of oxygen for eradication of target cells. In dentistry, this therapy is used to suppress the growth of microorganisms involved directly with dental decay and periodontitis process. There are evidences that curcumin dye is able to control microbial activity when illuminated with specific wavelength. The purpose of this study was to evaluate the in vitro efficacy of PDT using curcumin dye (Cur-C) in combination with a blue LED (L) device on a planktonic model of Streptococcus mutans ( S. mutans). Methods: Suspensions (0.5mL) containing S. mutans at 1×107CFUmL-1 were prepared and divided into 4 groups: Group C-L- (control: no treatment and 1 experimental condition), Group C+L- (curcumin at 3 different concentrations: 2000; 4000 and 8000μM and 3 experimental conditions), Group C-L+ (LED at 3 different dosages: 24, 48 and 72Jcm-2 and 3 experimental conditions), and Group C+L+ (PDT group: curcumin at respective concentrations combined to LED dosages and 9 experimental conditions). Samples of each experimental condition were cultured in Petri dishes of BHI agar. Incubation in micro-aerophilia at 37°C for 48h was performed for subsequent visual counting of CFU/mL. Data were transformed into log10 and analyzed by two-way ANOVA and Tukey's test at p<0.05. Results: Group C. +. L+, in specific experimental conditions, demonstrated a log bacterial reduction 70% higher than Group C. -. L-. Both groups C. -. L+ and C. +. L- presented a slight decrease in log bacterial counting. Conclusion: This in vitro method was able to reduce the number of S. mutans in a planktonic suspension. © 2013 Elsevier B.V.
Keywords: Photochemotherapy; S. mutans; agar; curcumin; bacterial count; blue led device; blue light; controlled study; in vitro study; nonhuman; petri dish; photodynamics; plankton; priority journal; radiation equipment; Streptococcus mutans; suspension; Bacteria (microorganisms)